2021
DOI: 10.1111/pbi.13567
|View full text |Cite
|
Sign up to set email alerts
|

MiR396‐GRF module associates with switchgrass biomass yield and feedstock quality

Abstract: Improving plant biomass yield and/or feedstock quality for highly efficient lignocellulose conversion has been the main research focus in genetic modification of switchgrass (Panicum virgatum L.), a dedicated model plant for biofuel production. Here, we proved that overexpression of miR396 (OE-miR396) leads to reduced plant height and lignin content mainly by reducing G-lignin monomer content. We identified nineteen PvGRFs in switchgrass and proved thirteen of them were cleaved by miR396. MiR396-targeted PvGRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 78 publications
(167 reference statements)
2
25
0
Order By: Relevance
“…The miR369 was reported to be involved in growth-regulating factors (GRF) silence, which may negatively regulate in disease resistance ( Chandran et al, 2018 ). The other research reported that the overexpression of miR369 has a negative influence on PH, which may be associated with biomass yield ( Liu et al, 2021 ), while in our study, miR369a-3p and miR369a-5p were downregulated in HNCy01 and HNCc22, which may have advantageous impacts on pepper growth. Based on these results, it is suggested that miRNA could play an important role in pepper heterosis.…”
Section: Discussionsupporting
confidence: 42%
“…The miR369 was reported to be involved in growth-regulating factors (GRF) silence, which may negatively regulate in disease resistance ( Chandran et al, 2018 ). The other research reported that the overexpression of miR369 has a negative influence on PH, which may be associated with biomass yield ( Liu et al, 2021 ), while in our study, miR369a-3p and miR369a-5p were downregulated in HNCy01 and HNCc22, which may have advantageous impacts on pepper growth. Based on these results, it is suggested that miRNA could play an important role in pepper heterosis.…”
Section: Discussionsupporting
confidence: 42%
“…Among the 1102 miRNA-mRNA pairs, there were 46 TFs, belonging primarily to WRKY, SBP, AP2/ERF, GRAS, MYB, NAC and bZIP families, and they showed contrasting gene expression patterns with their paired miRNAs. TFs from the families of WRKY, NAC, GRF, MYB, bZIP and AP2/ERF have been reported to be associated with sucrose accumulation (Huang et al, 2021;Li et al, 2020;Liu et al, 2021;Ohto et al, 2005;Song et al, 2013;Sun, Zhang, et al, 2019;Sun, Gao, et al, 2019;Wei et al, 2018). In this study, the TF-associated miRNA-mRNA pairs with contrasting expression included members of WRKY (c112674.graph_c1, c120167.graph_c0, c123264.graph_c0, c132973.graph_c1, c136438.graph_c0, c140583.graph_c0, c141561.graph_c0), NAC (c131322.…”
Section: Differential Expression Of Genes Related To Starch and Sugar Metabolism Pathways In Stem And Leaves Differentiates High-and Low-mentioning
confidence: 71%
“…While in pitaya, the downregulation of miR396 reached a minimum level (−37%) after 20 h [ 56 ], in common vetch, miR396 reached its highest level after 5 days, which was an upregulation by about two times. miR396 is a growth-regulating factor (GRF) [ 57 , 58 ], which causes different response degrees when plants are stressed at different growth stages.…”
Section: Discussionmentioning
confidence: 99%